Apreciação da fauna ictioparasitária em pesqueiro, tipo pesque-pague do município de Guariba - SP - Schalch, Sergio Henrique Canello [UNESP] (2002)
This research was designed to identify the main parasite diseases in different species of fish from fee-fishing at Guariba, State of São Paulo. This country is beated at latitude: 21°15'22 S, longitude 48°18'58 W, in altitude 595 meters. The research was developmento in period april, 1997 to march to 1999, seeking to verified the caractheristics of epizootic outbreaks, the Kind tissues lesions 408 fishes were examinated during a period of one year, the datas demonstred que 29,1% of them were infsted by the protozoans e metazoans. Leporinus macrocephalus shawed the highest parasitism by Trichodina sp, although Piaractus mesopotamicus and Cyprinus carpio were also parasited. Piscinoodinium pillulare infestation were found in L. macrocephalus, P. mesopotamicus, C. carpio e Colossoma macropomum. Monogenetics metazoa have largely been observed in L. macrocephalus, P. mesopotamicus, C. carpio, C. macropomum e cross-bred tambacu, despit of their incidence that was elevated in the summer for L. macrocephalus, spring for P. mesopotamicus and C. macropomum, and both seasons for cross-bred tambacu. Lernaea cyprinacea copepodes were observed in L. macrocephalus, P. mesopotamicus, C. carpio and cross-breeding tambacu, in spite of the fact thot C. carpio has demonstred high parasitism of adult form. L. macrocephalus, P. mesopotamicus e C. carpio showed susceptibility to Dolops sp parasitism, even though the main prevalence was observed during the summer and autumn seasons. P. mesopotamicus was the most susceptibility specie to the myxosporídeos, however this parasite were also identified in L. macrocephalus and cross-breeding tambacu. Severe gill lesions have been observed in L. macrocephalus e P. mesopotamicus caused by monogenetics, P. pillulare e Trichodina sp parasitism, such as: extensive hemorrhage area, sub epithelium edema, the primary and secondary lamina was hiperplastic, fusion of ...